Psychiatric Disorder and Incessant Tachyarrhythmia in a Child. (3rd April 2013) - Chau, Peter; Moore, Jeremy
Abstract : The case of a 14-year-old female with ectopic atrial tachycardia who had been followed for a history of anxiety and depression is presented. The patient was admitted to the intensive care unit after she attempted suicide, at which point there was electrocardiographic evidence of the atrial arrhythmia. During subsequent invasive electrophysiology study, a focus near the tricuspid annulus was localized and targeted for ablation, followed by resolution of the psychiatric symptoms. The case highlights the overlap between psychiatric complaints and true cardiac arrhythmia. A review of the literature is presented, with a special emphasis on distinguishing these two entities as well as a synopsis of this uncommon arrhythmia in the pediatric population.